2021
DOI: 10.3389/fneur.2021.787370
|View full text |Cite
|
Sign up to set email alerts
|

“Is It Removed During Dialysis?”—Cognitive Dysfunction in Advanced Kidney Failure—A Review Article

Abstract: Cognitive impairment is independently associated with kidney disease and increases in prevalence with declining kidney function. At the stage where kidney replacement therapy is required, with dialysis or transplantation, cognitive impairment is up to three times more common, and can present at a younger age. This is not a new phenomenon. The cognitive interactions of kidney disease are long recognized from historical accounts of uremic encephalopathy and so-called “dialysis dementia” to the more recent recogn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 128 publications
(159 reference statements)
0
20
0
Order By: Relevance
“…Other studies have also found similar decline in cognition with the presence of depression [45,47,48]. This can be explained by the effects of symptoms of depression on domains of cognition like executive functioning and processing speed [48,49]. A recent meta-analysis also shows that subjective stress influences the development of cognitive impairment [50].…”
Section: Discussionmentioning
confidence: 79%
“…Other studies have also found similar decline in cognition with the presence of depression [45,47,48]. This can be explained by the effects of symptoms of depression on domains of cognition like executive functioning and processing speed [48,49]. A recent meta-analysis also shows that subjective stress influences the development of cognitive impairment [50].…”
Section: Discussionmentioning
confidence: 79%
“…The presence of cognitive impairment in patients with CKD was first described by Dr. Thomas Addison in 1839 and, despite its significant association with poor treatment compliance, decision-making, readmissions, worsening kidney function, falls, and mortality, screening for cognitive impairment is not routinely conducted in the nephrology clinic [39]. More than half of HD patients with cognitive impairment are nonadherent to their medications [40].…”
Section: Cognitive Impairment and Chronic Kidney Diseasementioning
confidence: 99%
“…Edmonton Frail Scale [36] Based on the following www.krcp-ksn.org eGFR is associated with an 11% increase in cognitive impairment prevalence amongst those aged >55 years. There is a rapid decline in cognition for those with eGFR of <30 mL/min/1.73 m 2 , where more than three quarters of those undergoing dialysis and up to 2/3 of pre-dialysis patients may have underlying cognitive impairment [32,39]. The initiation of dialysis can cause a stepwise decline in cognition, especially executive function [41].…”
Section: ≤10mentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it is believed that the recurrent intradialytic decline in cerebral blood flow could predispose to cerebral ischemic injuries leading to vascular dementia. 4…”
mentioning
confidence: 99%